PERENCANAAN STRUKTUR MASJID BAITURRAHMAN RUMAH SAKIT AN-NISSA KOTA TANGERANG - Ilham Ilham (JOURNAL OF APPLIED SCIENCE (JAPPS), 2024)
With the increasing number of patients who seek treatment at an-Nisa Hospital, the prayer place that has been provided can not accommodate the number of patients and families of patients who pray at the mosque, for An-Nisa Hospital is committed to the construction of a mosque that is more spacious, comfortable and strategic in the area of An-Nisa hospital, for, This service activity exposes the contribution of the author as a civil engineering expert in helping the planning of the upper structure and the lower structure (foundation) of the mosque building. This mosque building is a 2-story building with an area of 957 m2 the implementation of this activity begins with a survey of the location, and then coordination with architects and MEP consultants to discuss the mosque's design. Furthermore, the analysis and design of the structure of the architectural design drawings have been agreed upon. The results of the design of the structure in the form of design drawings of the upper structure and the lower structure (Foundation) were used as reference images for the implementation of development. This mosque building is a reinforced concrete structure with concrete quality fc’ 25 M.Pa referring to SNI 2847-2019, the structural system used is a Special Moment Resisting Frame System (SRPMK)